El joropo en la historia de vida de una mujer (2024)
The research that gives rise to this degree work, under a descriptive methodological design articulating the life story as a central tool, as well as interviews and stories, will present, in a timeline, the significant experiences of Jenny Marcela Hernández Izquierdo's role as a dancer, instructor and cultural manager. The life of Jenny Marcela is an inspiring story of improvement and love for art. Born in Colombia, a country with immense cultural diversity and a rich history of artistic expressions, Jenny found more than a passion in joropo; she found his calling. Her dedication and talent have led her to be recognized both in her native country and on international stages, evidencing how culture and art can be powerful vehicles for personal and social change.